Taming the monster of child abuse in Nigeria (2016)
Child abuse in Nigeria is an age long plague which has over the years left traumatic effects on the victims of its harshness on the one hand ; and on the other has become a menace which seeks to seriously threaten the sanctity and stability of a credible future for Nigeria. This article gives a succinct overview of the issue of Child Abuse, particularly in Nigeria. It illuminates on the form of child abuse in Nigeria and gives an insight into new trends in which child abuse takes form of. In addition, the paper gives concise and graphic details on the consequences all forms of child abuse both on child victims and even on the government future of Nigeria. In discussing this, the writer gives an overview of the effect of the childs Right Act in the prevention and protection of children from child abuse in Nigeria. This is done to elaborate on the need for a drastic change and approach towards the issue of Child Abuse in Nigeria. The paper concludes by recommending measures the government can take to quell the menace of child abuse in Nigeria, and also recommends some salient modifications to the laws available on child Abuse in Nigeria.